AGE FACTOR IS RELATED TO ANXIETY IN BREAST CANCER PATIENTS UNDERGOING CHEMOTHERAPY - Sesrianty, Vera; Yani Fitri, Rizki; Fernandes, Andrye (Jurnal Keperawatan Sriwijaya, 2026)
Aim : This study aimed to determine the relationship between age and anxiety in breast cancer patients undergoing chemotherapy. Method: This was a quantitative cross-sectional study. A purposive sampling technique was used to select 70 respondents undergoing chemotherapy. Data were analyzed using the chi-square test. The study used a questionnaire to measure age characteristics, including early adulthood and middle adulthood by Hurlock, and anxiety levels using the HARS questionnaire.  Results : The study showed that the majority of respondents were aged ≥36 (70.0%), and the majority experienced severe anxiety (65.7%). Statistical tests revealed a significant relationship between age and anxiety in breast cancer patients undergoing chemotherapy (p = 0.000). Conclusion : There is a relationship between age and anxiety in breast cancer patients undergoing chemotherapy. The results of this study are expected to provide a basis for nursing staff in developing more specific psychosocial interventions tailored to the patient's age characteristics, thereby improving patient safety, quality of nursing care, and quality of life for breast cancer patients.